Can PhET simulate basic electronics circuits for undergraduate students? - Syifaul Fuada; Muhamad Dzikri Danuarteu; Sarah Agustin; Anindya Afina Carmelya; Iffah Fadhilah; Yee Mei Heong; Adisorn Kaewpukdee (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
PhET is one of the most powerful and impressive simulator innovations, widely used in the STEM-based learning process. Based on literature reviews, students are allowed to independently practice their skills and understanding of the material concept using this tool. PheT involves students in process competencies comprehensively and also provides a highly interactive virtual environment for STEM materials, including basic electronics, a sub-category of physics. This tool can also be easily accessed online at https://phet.colorado.edu/ or offline with a note that the user should download and install the application on a PC. An interesting question regarding this education tool is,